استجابة المرضى المصابين بسرطان البروستات الحساس للعلاج الهرموني لجرعة منخفضة من الكيتوكونازول - عبد الله نادر (Latakia University Journal -Medical Sciences Series, 2017)
تعتبر المشاركة بين الكيتوكونازول بجرعة منخفضة مع الستيروئيدات من العلاجات الهرمونية الفعالة في حال سرطان البروستات الحساس للمعالجة الهرمونية كخط علاجي هرموني ثاني والمستخدمة منذ أكثر من 30 سنة بسبب دوره في تثبيط تصنيع الأندروجينات الكظرية. يهدف هذا البحث إلى تقييم الاستجابة للجرعات المنخفضة من الكيتوكونازول عند مرضى سرطان البروستات الحساسين للمعالجة الهرمونية والمراجعين لمركز المعالجة الكيميائية والشعاعية بمشفى تشرين الجامعي بالفترة بين كانون الثاني 2010 وحتى كانون الثاني 2016 والمعالجين بالضهي الجراحي أو الدوائي ولديهم ارتفاع PSA(الواسم الورمي النوعي لسرطان البروستات) بدون ظهور نقائل عظمية جديدة, وذلك بعد اعطاء الكيتوكونازول 200 ملغ 3 مرات يوميا بالمشاركة مع البريدنيزولون 5ملغ مرتين يوميا مع متابعة المعالجة حتى تفاقم الإصابة أو ظهور سمية زائدة. شملت الدراسة 50 مريض وتمت معايرة ال PSA لديهم قبل تناول العلاج ثم شهريا حتى تفاقم الإصابة أو ظهور سمية دوائية. لوحظ معدل الاستجابة عند 23 مريض وبنسبة 46% حدث لديهم نقص PSA≥ 50% ، 12 مريض حدث لديهم نقص PSA بين 25- 50% ، 5 مرضى حدث لديهم نقص أقل من 25% بينما 10 مرضى لم يستجيبوا أبدا مع متوسط مدة استجابة حوالي 5،4 شهر. بالمقابل كانت السمية قليلة والتحمل جيد للدواء، فقط 3 مرضى من أصل 50 مريض لم يتمكنوا من متابعة المعالجة. لقد أظهرت الدراسة فعالية متوسطة للكيتوكونازول يجرعة منخفضة بالمشاركة مع البريدنيزولون مع تحمل جيد وتوفير اقتصادي بالمقارنة مع الأجيال الحديثة من مثبطات الأندروجين الكظرية ذات التكلفة الاقتصادية العالية جدا. Background: low –dose ketoconazole (LDK) in combination with steroids has been recognized as an effective secondary hormonal therapy in androgen-independent prostate cancer (AIPC), we hypothesized that low-dose ketoconazole would likewise possess efficacy and tolerabilitiy in the (AIPC). Methods: in a single institution (Tishreen University Hospital, Lattakia), patients with AIPC treated with LDK (at a dose of 200 mg orally 3 times daily ) as secondary hormonal therapy with concomitant steroids were retrospectively identified, After experiencing a rising prostate –specific antigen (PSA) level. Results: 21 of 50 eligible patients)42%) treated with LDK experienced PSA declines ≥ 50% after the start of treatment, while there were 12 patients with low PSA between 25-50% with a median duration of response (5.4 months) 7 patients less than 25 % decrease, while 10 patients did not never respond. The most common complications is the fatigue and general debility in 18 patients , digestive disorders in 21 patients (Summit, nausea and diarrhea) , muscle disorders in 3 patients, and Metabolic disorders in five patients The incidence of drug toxicity grade 3-4 is very few. There were only three patients not able to continue the treatment due to severe side effects. Conclusion: low dose ketokonazole and Predenisolone is a well – tolerated, relatively inexpensive and clinically active treatment option. PSA response to low – dose ketoconazole historically comparable to that of Abiraterone in patients with AIPC.